Physiological and multi-omics analysis revealed the mechanism of arbuscular mycorrhizal fungi to cadmium toxicity in green onion - Kunhao Xie; Yixuan Chen; Xiaoqin Wang; Xiaoya Zhou; Yizhe Cheng; Xianchang Yu; Jun Wang; Mintao Sun; Yansu Li; Chaoxing He (Ecotoxicology and Environmental Safety)
Cadmium (Cd) is a highly toxic agricultural pollutant that inhibits the growth and development of plants. Arbuscular mycorrhizal fungi (AMF) can enhance plant tolerance to Cd, but the regulatory mechanisms in Allium fistulosum (green onion) are unclear. This study used a Cd treatment concentration of 1.5 mg·kg−1, which corresponds to the risk control threshold for soil pollution in Chinese agricultural land, to examine the effects and molecular mechanisms of AMF inoculation on the growth and physiology of green onion under Cd stress. AMF formed an effective symbiotic relationship with green onion roots under Cd stress, increased plant biomass, improved root structure and enhanced root vitality. AMF-colonized green onion had reduced Cd content in roots and leaves by 63.00 % and 46.50 %, respectively, with Cd content being higher in the roots than in the leaves. The ameliorative effect of AMF on Cd toxicity was mainly due to a reduction in malondialdehyde content in leaves (30.12 %) and an enhancement of antioxidant enzyme activities (peroxidase, catalase, superoxide dismutase, glutathione reductase and reduced glutathione) that mitigated damage from excessive reactive oxygen species. In addition, AMF induced secretion of easily extractable glomalin soil protein and total glomalin-related soil protein and inhibited the translocation of Cd to the shoots. Transcriptomic and metabolomic correlation analyses revealed that differentially expressed genes and metabolites in AMF-inoculated green onion under Cd stress were predominantly enriched in the “phenylpropanoid biosynthesis” and “phenylalanine metabolism” pathways, upregulated the expression of the HCT, PRDX6, HPD, MIF, and HMA3 genes, and accumulation of the phenylalanine, L-tyrosine, and 1-O-sinapoyl-β-glucose metabolites. Thus, AMF enhance Cd tolerance in green onions by sequestering Cd in roots, restricting its translocation, modulating antioxidant defenses and inducing the expression of genes involved in the phenylpropanoid biosynthesis and phenylalanine metabolism pathways. Collectedly, we for the first time revealed the mechanism of AMF alleviating the toxicity of Cd to green onion, providing a theoretical foundation for the safe production and sustainable cultivation of green onion in Cd-contaminated soils.